Keterampilan Literasi Numerasi Siswa Sekolah Dasar: Studi Kasus Sekolah Dasar Daerah 3T - Anggraeni, Desak Made (Universitas Pendidikan Mandalika (UNDIKMA), 2024)
Numeracy skills are one of the abilities needed to increase fighting power to face the challenges of the 21st century. This research aims to analyze the numeracy skills of elementary school students in the 3T area in understanding STEM-based numeracy literacy questions. This research is descriptive, uses a qualitative approach, and uses a case study method. The objects of this research were sixth-grade elementary school students in the 3T area. The data collection techniques used were STEM-based numeracy tests and interviews. The research instrument was a numeracy literacy test with six questions adapted from the minimum competency assessment (AKM) questions. The research results showed that students still needed higher numeracy literacy skills and help answering questions correctly. The interviews showed that most of the questions given had never been encountered, and students could not use their reasoning in choosing the right strategy for solving problems. Based on the research results, the numeracy literacy skills of students in the 3T area still need to improve. Students still need to work on numeracy questions related to everyday life. Students use the guessing method and answer according to the visual display or the numbers in the problem or question.